2009
DOI: 10.1097/dcc.0b013e3181a4743b
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Impact of Implantable Cardioverter Defibrillator on Their Recipients

Abstract: This 12-month longitudinal prospective study tracked the depression and anxiety levels of implantable cardioverter defibrillator recipients after implantation of the device. Depression and anxiety levels dropped significantly over time. These findings suggest that interventions should be implemented early because the needs are greatest in the first few weeks after device implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
3
8
0
Order By: Relevance
“…However, the discrepancy may also be due to the technical advances in ICD devices. The rate of anxiety disorders dropped significantly over the course of 5 months, which is in contrast to some studies, but is in line with most other longitudinal studies . It should be noted that PTSD was assessed by the PDS at baseline and diagnosed by the SCID at follow‐up.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, the discrepancy may also be due to the technical advances in ICD devices. The rate of anxiety disorders dropped significantly over the course of 5 months, which is in contrast to some studies, but is in line with most other longitudinal studies . It should be noted that PTSD was assessed by the PDS at baseline and diagnosed by the SCID at follow‐up.…”
Section: Discussionsupporting
confidence: 86%
“…The prevalence rates of anxiety among ICD recipients differ widely from 8% to 63%, which might be due to the choice of assessment instruments, definitions of psychopathology, small sample sizes, patient selection bias, or the timing of assessments . Most longitudinal studies have found a decrease in anxiety over time, while others report anxiety as a chronic problem …”
Section: Introductionmentioning
confidence: 99%
“…1997). One possible explanation could be that the recipients in the present study had lived with their ICD from 6–24 months and already had adapted to the changed life situation, with the level of depression decreasing over time as described by Wheeler et al. (2009).…”
Section: Discussionmentioning
confidence: 92%
“…As indicated by the literature, both directions are plausible. The Triggers of Ventricular Arrhythmias (TOVA) study showed that depression increases the risk of ICD shocks, 15 while ICD shocks have also been associated with increased depression scores, 16 although not all studies support the latter relationship 11,17 …”
mentioning
confidence: 99%
“…The Triggers of Ventricular Arrhythmias (TOVA) study showed that depression increases the risk of ICD shocks, 15 while ICD shocks have also been associated with increased depression scores, 16 although not all studies support the latter relationship. 11,17 The chicken-and-egg mystery remains difficult to resolve. In the meantime, there are steps that we can take to improve the value of research in this area.…”
mentioning
confidence: 99%